SYURA DAN DEMOKRASI: ANTARA TEORI DAN PRAKTEKNYA DALAM DUNIA ISLAM - Anggi Wahyu Ari (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Shura and democracy are two concepts that seem substantially almost exactly the same, but these two concepts have differences because both have differences historically, culturally and structurally. The differences are further aggravated by the suggestion and the image that grows in some people that shura is identical with the teachings of Islam which is derived from Allah. In, fact democracy is a product of man (the West) while Shura is Islamic concept of authority. This paper tries to see how the difference between shura and democracy and whether the difference was highly significant that what is thought by some people, that we have to replace the democratic system with the shura.